Advanced Chromatographic Technique for the Analysis of Sugars Extracted from the Peels of Black Grape (Vitis vinifera L.) - Chidan Kumar, C.S.; Mythily, R.; Chandraju, S. (Asian Journal of Chemistry, 2012)
A rapid, sensitive extraction method was developed using the mixture methanol-dichloromethane- water (MDW) (0.3:4:1v/v/v) and MeOH-H2O phase was assayed for sugar analysis. Photodiode-array detection (DAD) has been used to prove the extracted compound is UV inactive, high-performance liquid chromatography (HPLC) with evaporative light scattering detector (ELSD) coupled to electrospray ionization mass spectrometric (ESI-MS) detection in the positive ion mode gave MS and MSn fragmentation data, which were employed for their structural characterization. Various standard sugars were spotted using the solvent system n-propanol-ethyl acetate-water (13:37:7, v/v/v) in the cellulose layer for TLC analysis which indicated the presence of aldohexose glucose and ketohexose fructose. This is the first assay of the sugar profile of the black grape peels, which can be further developed for characterization and evaluation of their quality with regards to their sugar composition.